PERAN GURU DALAM MOTIVASI BELAJAR PADA KETRAMPILAN BERBICARA SISWA KELAS I MATA PELAJARAN BAHASA INDONESIA DI SEKOLAH PENGGERAK SDN SUMBEREJO II - Siti Nur Janah; Salsa Ayu Sabrina; Isa Nur Fadhilah; Fathimatuz Zahro; Rizka Nur Oktaviani (INVENTA: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
In this study, the aim was to find out the teacher's role in learning motivation in improving students' speaking skills. The type of method used in this research is to use qualitative research methods. This research method is qualitative with descriptive qualitative research type. The data collection techniques used by researchers are through observation, interviews, and documentation. The data analysis technique used by researchers is qualitative data with the Miles and Huberman model through several activities namely data collection, data reduction, data presentation, and verification. The results of research on the teacher's role in motivating students greatly influence students' speaking skills. There are many things that a teacher can do to motivate students, including cultivating the hopes and aspirations of students. Teachers always motivate students to have high learning enthusiasm. In order for students to have an enthusiasm for learning, the teacher not only motivates students but the teacher must also bring up the desire and desire for student learning, raise the hopes and aspirations of students, then provide rewards in learning by taking strategies through giving appreciation or rewards, as well as a learning environment that is conducive to learning. conducive so that students can learn well. With this, students can be skilled in speaking and precise in choosing words and logical sentence structures.